Techno-economic and sustainability models for integration of cassava waste-based biorefineries into cassava starch processes based on process simulation and a systems modelling approach - Padi, Richard Kingsley (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.